1995
DOI: 10.1111/j.1432-1033.1995.tb20483.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte p56L32 is A RNA/DNA-Binding Protein which Interacts with Conserved Elements of the Murine L32 Ribosomal Protein mRNA

Abstract: In previous studies of the ribosomal protein L32 mRNA, we demonstrated that a conserved polypyrimidine tract found in the 5'-untranslated region (5'-UTR) was required for translational regulation in vivo and that a 56-kDa protein (~5 6~~~) from T-lymphocytes specifically interacts with this sequence [Kaspar, R. L., Kakegawa, T., Cranston, H., Morris, D. R. & White, M. W. (1992) J. Biol. Chem. 267, Here we show that ~5 6~~~ binding to the L32 5'-UTR is complex and requires other 5'-UTR RNA sequences in conjunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
(3 reference statements)
0
8
0
Order By: Relevance
“…Two of them, named A and B (57 kDa and 47 kDa), were found to interact with the pyrimidine tract, while the others, C and D (31 kDa and 24 kDa), were shown to bind the downstream region of the 5' UTR. Similarly, a protein of 57 kDa has been described to bind the pyrimidine tract of mouse rp-L32 mRNA (Kaspar et al, 1992;Severson et al, 1995). Here, we report the purification and characterization of the Xenopus 57 kDa protein that binds the L4-mRNA pyrimidine tract, and its identification as La, the Xenopus homologue (Scherly et al, 1993) of human La autoantigen (reviewed by Pruijn et al, 1990).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Two of them, named A and B (57 kDa and 47 kDa), were found to interact with the pyrimidine tract, while the others, C and D (31 kDa and 24 kDa), were shown to bind the downstream region of the 5' UTR. Similarly, a protein of 57 kDa has been described to bind the pyrimidine tract of mouse rp-L32 mRNA (Kaspar et al, 1992;Severson et al, 1995). Here, we report the purification and characterization of the Xenopus 57 kDa protein that binds the L4-mRNA pyrimidine tract, and its identification as La, the Xenopus homologue (Scherly et al, 1993) of human La autoantigen (reviewed by Pruijn et al, 1990).…”
Section: Introductionmentioning
confidence: 79%
“…It appears that other proteins, which have been shown to interact with the 5' UTR of r-protein mRNA downstream of the pyrimidine tract (Cardinali et al, 1993), might be involved in the regulation. It has been found that this downstream region, together with the pyrimidine tract, is relevant in translational regulation in mammalian cells (Avni et al, 1994) and that mutations in this sequence alter protein binding (Severson et al, 1995). However, other elements that may be implicated in a more complex mechanism have to be kept in mind.…”
Section: Binding Analysis Of Mutated La Rna Pyrimidine Tractsmentioning
confidence: 99%
“…This protein may also be involved in providing the observed cell specificity toward the effect of TOP on Pabp1 mRNA translation. Although TOP binding proteins have been shown for some TOP mRNAs (55)(56)(57)(58)(59)(60)(61), their role in mRNA translation is uncertain, because the level of TOP binding activity does not change under conditions that inhibit translation of TOP mRNAs (37). It is not clear whether all TOP elements behave similarly.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies some proteins were identi®ed to bind speci®cally in vitro to the pyrimidine tract and to the region downstream of the 5 H UTR of Xenopus L4 mRNA (Cardinali et al, 1993). Similarly, a protein has been described to bind the pyrimidine tract of mouse rp-L32 mRNA (Kaspar et al, 1992;Severson et al, 1995). In a recent study the rp-mRNA pyrimidine tract binding protein was identi®ed as the Xenopus homologue of human La autoantigen (Scherly et al, 1993) and its binding was dependent on the interaction with at least one protein factor.…”
Section: This Type Ofmentioning
confidence: 96%